S53 UK doctors current perceptions of E-cigarettes (vaping). (December 2018) - Corkill, J; Faber, S; Irshad, F; Valerio, C; Moonsie, I; Makker, H; Lozewicz, S; Sheinman, B; Jayaraman, B; Mangera, Z
Abstract : Background: Over recent years prominent organisations including the Royal College of Physicians and Public Health England have strongly advocated the use of e-cigarettes (vaping) as a harm reduction strategy. We carried out a survey to explore the perceptions of clinician's on the safety of E-cigarettes and its role in helping smokers quit. Method: A nine item electronic survey was distributed via email and social media to UK-based doctors and surgeons at various stages of training. Questions were answered using a five point Likhert scale. They related to areas including perceptions of E-cigarettes, their individual experience discussing E-Cigarettes with patients and their broader knowledge of 'safer smoking'. Results: A total of 150 responses were received. Of those, 57 were Consultants, 13 GPs, 34 ST3+ (or equivalent, 39 core training or below (or equivalent), and 7 did not disclose. Whilst the majority (73%) of responders either agreed or strongly agreed that the health risks of E-cigarettes were substantially lower than smoking, there was an even distribution of support and opposition towards them being available to prescribe under the NHS. Similarly, there was much variation in how confident physicians felt discussing e-cigarettes with patients. The majority (68%) of responders agreed or strongly agreed that they would recommend e-cigarettes as a smoking cessation treatment to those that have previously tried and failed other means. A much smaller majority would recommend them to patients that had never tried to quit. 40% of responders were never asked their advice on e-cigarettes, the majority of these being more junior doctors. Full results will be presented. Conclusion: This survey suggests that most doctors surveyed believe e-cigarettes are safer than smoking, however there is clear uncertainty about their longer-term health implications. Doubts exists as to whether they should be widely available on the NHS. E-cigarettes are still not a common topic of discussion between clinicians and patients, especially amongst more junior clinicians. This survey suggests a continued lack of consensus amongst clinicians, in terms of the role of e-cigarettes in helping smokers quit and they urgently require further support and evidence based guidance in their clinical practice.